ABRUPTIO PLACENTAE AND ITS COMPLICATIONS AT AYUB TEACHING HOSPITAL ABBOTTABAD - Sarwar, Iram; Abbasi, Aziz un Nisa; Islam, Ansa (Journal of Ayub Medical College Abbottabad, 2006)
Background: Abruptio placentae remains a major cause of perinatal morbidity and mortality globally, though of most serious concern in the developing world. As most known causes of abruptio placentae are either preventable or treatable, an increased frequency of the condition remains a source of medical concern. Methods: The present study was undertaken at the Department of Obstetrics and Gynaecology, Unit B, of the Ayub Teaching Hospital, Abbottabad, Pakistan, from July 2003 to June 2004. Patients of abruptio placentae were selected from all cases of 28 weeks or greater gestation, presenting with ante partum haemorrhage during the study period. Patients underwent a complete obstetrical clinical workup including history, general physical examination, abdominal and pelvic examination. Relevant investigations such as laboratory tests and imaging were performed. Patients were managed according to maternal and fetal condition. Any maternal and/or fetal complications were noted and recorded. All data were collected on predesigned proformas and analyzed by computer. Results: A total of 53 cases of abruptio placentae were recorded out of 1194 cases (4.4%) admitted for delivery during the study period, giving a rate of 44 cases of abruptio placentae per 1000 deliveries. Induction of labour was required in 27 (50.9%) cases, while caesarean section was performed in 16 (30.2%) cases. Major complications were intra uterine fetal demise (31/53, 58.5%), fetal distress (8/22 live births, 36.4%) and post partum haemorrhage, which occurred in 10 (18.9%) cases. Conclusions: A higher than expected frequency of abruptio placentae exists in our setting and the consequences of abruptio placentae for neonatal mortality outcome are alarmingly high. The majority of patients presented with intra uterine death so that any management protocol directed at abruptio placentae or its consequences is of little help in preventing perinatal mortality. Key Words: Abruptio placentae, ante partum haemorrhage, perinatal mortality.